Auto Following Trolley - AZIMI, NURULHUDA NATASHA; ARMAN SABRI, AMIRAH SYAFIQAH; SHAMSUL, NURHAZWANI HADHIRAH; AHMAD, NUR AZLIZA (Multidisciplinary Applied Research and Innovation, 2023)
Supermarkets are practically fully developed nowadays, thanks to several technology breakthroughs. People buy various things from supermarkets and place them on a trolley since this is the most convenient way to transport goods in supermarkets or shopping malls. When shopping at supermarkets or food stores, a shopping trolley is a must-have item. Customers, on the other hand, must manually push the trolley during the whole purchasing procedure. To circumvent these issues, the study team devised a sophisticated and successful approach. As a result, the major goal of this project is to develop and produce a trolley that is user-friendly for humans, decreasing their load and increasing their productivity, as well as to create an autonomous trolley capable of transferring objects from one point to another. This paper proposes an auto following trolley where the ultrasonic sensors in the trolley is used to determine the user and the trolley and move appropriately. The trolley’s connectivity is also maintained via the remote controller which can opearate the trolley using both the RF receiver and the RF transmitter. A microcontroller module unit controls the trolley. It has the ability to stop, turn right, turn left, go ahead and move backward. It can track them everywhere they go when in range. The created model was contrained with a barrier, similar to supermarkets and retail malls in order to move according to the wishes of the user and are controlled by the remote controller that they have.